2001
DOI: 10.1055/s-2001-17550
|View full text |Cite
|
Sign up to set email alerts
|

History, Heterogeneity, Developmental Biology, and Functions of Quiescent Hepatic Stellate Cells

Abstract: In 1876, von Kupffer described liver Sternzellen (star-shaped cells). The functions of these cells remained enigmatic for 75 years until Ito observed lipid-containing perisinusoidal cells in human liver. In 1971, Wake demonstrated that the Sternzellen of von Kupffer and the fat-storing cells described by Ito were identical. Wake also established that these cells were important sites of vitamin A storage. Soon thereafter, Kent and Popper demonstrated that the stellate cells were intimately linked to the pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
580
1
15

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 684 publications
(606 citation statements)
references
References 169 publications
(253 reference statements)
10
580
1
15
Order By: Relevance
“…2 Controversies exist about the embryonic origin of HSCs, because they express proteins of all three germ layers. 3 Bone marrow stem cells are able to generate cells of all germ layers, and it was suggested that the bone marrow might be a source of stellate cells in adult vertebrate liver. 4,5 This indicates a mesodermal origin of stellate cells, which was confirmed by a very recent study.…”
Section: S Tellate Cells Reside Within the Perisinusoidal Space Ofmentioning
confidence: 99%
“…2 Controversies exist about the embryonic origin of HSCs, because they express proteins of all three germ layers. 3 Bone marrow stem cells are able to generate cells of all germ layers, and it was suggested that the bone marrow might be a source of stellate cells in adult vertebrate liver. 4,5 This indicates a mesodermal origin of stellate cells, which was confirmed by a very recent study.…”
Section: S Tellate Cells Reside Within the Perisinusoidal Space Ofmentioning
confidence: 99%
“…Under basal conditions, hepatic stellate cells are in a quiescent state and function to store retinoids within the liver (Blomhoff et al, 1990;Geerts, 2001). However, upon activation, these cells undergo transformation, assuming a myofibroblast morphology and expressing smooth muscle actin (Ramadori et al, 1990;Schmitt-Graff et al, 1991).…”
mentioning
confidence: 99%
“…Such observations were registered at a time when the concept about the irreversibility of hepatic fibrosis was taken for granted. Nowadays, such possibility is admitted while the cases of successful liver fibrosis rever- sion are being published (Geerts 2001, Desmet & Roskams 2004, which included even cases of far advanced cirrhosis (Arthur 2002, Massarrat et al 2004.…”
mentioning
confidence: 99%